Morbidity Pattern and Drug Prescribing Study in Pregnant Women of Rural Part of Charotar Region - Suthar, Jalpa; Patel, Riya (Indian Journal of Pharmacy Practice)
Background: Pregnancy is a normal physiological condition where drug treatment presents a special concern because certain drugs that harm to the fetus due to the potential teratogenic effects of drugs. Therefore, the present study was planned to carry out with the objective to evaluate the drug prescribing pattern, morbidity and categories of safe drug prescribing among all the pregnant women. Materials and Methods: A cross-sectional observational study was carried out in 400 pregnant women who attended inpatient and outpatient department at CHARUSAT Hospital during 8 months of study. Demographic details, prescribed drugs, medical history and diagnosis were recorded in CRF. The prescription pattern was assessed and drugs were classified based on USFDA Risk Classification. Results: In present study, iron (82.65%), folic acid (53.62%), calcium (58.51%) and vitamins (82.84%) were found the most frequently prescribed drugs during pregnancy. Anti-emetics, PPIs and H2 blockers, Antibiotics, Anti-hypertensive agents prescribed drugs during labor. The majority of drugs (49.05%) prescribed were from category B. Anemia (66.75%) was found to be a top most morbidity in pregnant women. Other obstetric morbidities like PIH, Breech presentation, Oligohydramnios, Meconium stain Lycor were observed during study period. Conclusion: Majority of the drugs (49.05%) prescribed as per FDA category B. No drug was prescribed belonging to the category X in study. Anemia was found in (66.75%) of pregnant women. Whereas PIH was found in (4%) of pregnant women.
Keywords: Drug prescribing; Antenatal; Maternal morbidity; Pregnancy; Anemia; Pregnancy Induced Hypertension.